Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2139/ssrn.3301739
|View full text |Cite
|
Sign up to set email alerts
|

Does Education Affect Attitudes Towards Immigration? Evidence from Germany

Abstract: Using data from the German Socio-Economic Panel and exploiting the staggered implementation of a compulsory schooling reform in West Germany, this article finds that an additional year of schooling lowers the probability of being very concerned about immigration to Germany by around six percentage points (20 percent). Furthermore, our findings imply significant spillovers from maternal education to immigration attitudes of her offspring. While we find no evidence for returns to education within a range of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Nevertheless, the later study suffers from similar problems as those I argue to beset PvW's study. 2 The lack of wage returns from the German schooling extensions is also surprising in light of evidence for significant nonpecuniary effects of this reform on health (Kemptner et al, 2011), fertility (Cygan-Rehm & Maeder, 2013), intergenerational transmission of education (Piopiunik, 2014), and even natives' attitudes toward immigrants, which persist beyond the treated generation (Margaryan et al, 2019). Related research for Germany also indicates positive wage returns to education beyond compulsory schooling (Kamhöfer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the later study suffers from similar problems as those I argue to beset PvW's study. 2 The lack of wage returns from the German schooling extensions is also surprising in light of evidence for significant nonpecuniary effects of this reform on health (Kemptner et al, 2011), fertility (Cygan-Rehm & Maeder, 2013), intergenerational transmission of education (Piopiunik, 2014), and even natives' attitudes toward immigrants, which persist beyond the treated generation (Margaryan et al, 2019). Related research for Germany also indicates positive wage returns to education beyond compulsory schooling (Kamhöfer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research in Germany concludes that lower levels of education translates in a amplification of the perception of ethnic conflict, particular after certain events in the life course (Kratz, 2021). Other work, also in Germany, finds that education is directly linked to greater tolerance of immigration (Margaryan et al, 2019). In contrast, work in Sweden concluded that education has no direct causal relationship with attitudes towards immigration (Finseraas et al, 2018).…”
Section: Education Mobility and Attitudes Towards Migrantsmentioning
confidence: 95%
“…Regarding the related literature that analyzes changes to the compulsory schooling laws in Germany, find zero wage returns-although this result has recently been challenged by Cygan-Rehm (2021). Considering non-pecuniary outcomes, reforminduced schooling had a positive effect on long-term health for men with mixed evidence for BMI and smoking (Kemptner et al, 2011) and on attitudes towards migration (Margaryan et al, 2021), negative effects on completed fertility (Cygan-Rehm and Maeder, 2013), and no effect on crystallized intelligence (Kamhöfer and Schmitz, 2016) or political participation (Siedler, 2010). Kassenboehmer et al (2021) analyze how changes to compulsory schooling in two Australian states affect the Big Five traits and locus of control.…”
Section: A16mentioning
confidence: 99%